Community Capacity Building in Social Forestry Development: A Review - Pujo Pujo; Tubagus Furqon Sofhani; Budhi Gunawan; Tati Suryati Syamsudin (The Institute for Research and Community Services, Institut Teknologi Bandung, 2018)
Abstract. Social forestry has shifted the forestry development paradigm from conventional forest management to community-based forest management. The history of community-based forest management in Java began with the Dutch colonial policy on forest production in 1873 and today it has grown widely, both within and outside forest areas. However, social forestry has not been able to overcome population pressure problems in the form of deforestation and forest degradation. Therefore, it is crucial to recognize and elevate the role of local communities in forest management. Success of social forestry can be achieved by developing cooperation through capacity building of local communities with community-based forest management. To develop community capacity, it is necessary to understand the basic concept of community capacity building in the social forestry system. A review of community capacity in social forestry is useful for developing a conceptual framework of local community capacity in the development of the social forestry system. Community capacity in the social forestry system is developed to realize forest sustainability and community welfare around the forest.Keywords: Community, capacity building, social forestry.Abstrak. Konsep perhutanan sosial telah menggeser paradigma pembangunan hutan dari pengelolaan hutan secara konvensional ke pengelolaan hutan dengan berbasis masyarakat. Sejarah pengelolaan hutan berbasis masyarakat di Jawa dimulai dengan adanya kebijakan kolonial Belanda tentang produksi hutan pada tahun 1873 dan saat ini kebijakan tersebut telah tumbuh secara luas, baik di dalam maupun di luar kawasan hutan. Namun, kehutanan sosial belum mampu mengatasi masalah kehutanan yang disebabkan oleh tingginya permintaan seperti deforestasi dan degradasi hutan. Oleh karena itu, mengenali dan meningkatkan peran serta masyarakat lokal dalam pengelolaan hutan perlu dilakukan. Keberhasilan kehutanan sosial dapat dicapai dengan mengembangkan kerjasama melalui pembangunan kapasitas masyarakat lokal melalui pengelolaan hutan berbasis masyarakat. Untuk mengembangkan kapasitas masyarakat, pemahaman tentang konsep dasar peningkatan kapasitas masyarakat dalam sistem kehutanan sosial diperlukan. Tinjauan kapasitas masyarakat dalam kehutanan sosial berguna untuk mengembangkan kerangka kerja konseptual kapasitas masyarakat lokal dalam pengembangan sistem kehutanan sosial. Kapasitas masyarakat dalam sistem kehutanan sosial dikembangkan untuk mewujudkan kelestarian dan keberlanjutan hutan, serta kesejahteraan masyarakat di sekitar hutan.Kata kunci: Komunitas, peningkatan kapasitas, perhutanan sosial.